Which Emergency Medicine Milestone Sub-competencies are Identified Through Narrative Assessments? - Diller, David (West J Emerg Med, 2020)
INTRODUCTION: Evaluators use assessment data to make judgments on resident performance within the Accreditation Council for Graduate Medical Education (ACGME) milestones framework. While workplace-based narrative assessments (WBNA) offer advantages to rating scales, validity evidence for their use in assessing the milestone sub-competencies is lacking. This study aimed to determine the frequency of sub-competencies assessed through WBNAs in an emergency medicine (EM) residency program. METHODS: We performed a retrospective analysis of WBNAs of postgraduate year (PGY) 2–4 residents. A shared mental model was established by reading and discussing the milestones framework, and we created a guide for coding WBNAs to the milestone sub-competencies in an iterative process. Once inter-rater reliability was satisfactory, raters coded each WBNA to the 23 EM milestone sub-competencies. RESULTS: We analyzed 2517 WBNAs. An average of 2.04 sub-competencies were assessed per WBNA. The sub-competencies most frequently identified were multitasking, medical knowledge, practice-based performance improvement, patient-centered communication, and team management. The sub-competencies least frequently identified were pharmacotherapy, airway management, anesthesia and acute pain management, goal-directed focused ultrasound, wound management, and vascular access. Overall, the frequency with which WBNAs assessed individual sub-competencies was low, with 14 of the 23 sub-competencies being assessed in less than 5% of WBNAs. CONCLUSION: WBNAs identify few milestone sub-competencies. Faculty assessed similar sub-competencies related to interpersonal and communication skills, practice-based learning and improvement, and medical knowledge, while neglecting sub-competencies related to patient care and procedural skills. These findings can help shape faculty development programs designed to improve assessments of specific workplace behaviors and provide more robust data for the summative assessment of residents.